Optimalisasi Potensi Daiyah melalui Pelatihan Peningkatan Kapasitas Strategi Dakwah dan Public Speaking di Kabupaten Ngawi - Yuliastutik; Badriyah, Laila (Program Studi Manajemen FEB UNM, 2025)
Ngawi Regency has significant potential in female Islamic preachers (daiyah), as reflected in the presence of women preachers, hafidzah, Qur’anic teachers, and community-based da’wah activists. However, this potential has not been fully supported by adequate strategic and communicative capacities, particularly in responding to contemporary da’wah challenges that require adaptive communication skills. This community service program aimed to enhance the capacity of daiyahthrough training in da’wah strategies and public speaking skills to enable more effective and contextual delivery of religious messages. The activity was conducted on September 24, 2025, in Ngawi Regency using a Participatory Action Research (PAR) design integrated with the Asset-Based Community Development (ABCD) approach. This approach positioned daiyah as active subjects of the program by emphasizing the identification and optimization of participants’ existing assets. The program stages included identifying potentials and needs, participatory planning of training activities, implementation of training actions, and collective reflection and evaluation. The results indicated an improvement in participants’ understanding of the importance of well-planned da’wah strategies tailored to audience characteristics. In addition, practice-based training contributed to strengthening public speaking skills and increasing the self-confidence of daiyah in delivering da’wah in public settings. The PAR–ABCD approach proved effective in fostering reflective and sustainable learning processes in strengthening da’wah capacity based on local potential.